Moods in Clinical Depression Are More Unstable than Severe Normal Sadness - Bowen, Rudy; Peters, Evyn; Marwaha, Steven; Baetz, Marilyn; Balbuena, Lloyd (Frontiers in Psychiatry, 2017)
Objective: Current descriptions in psychiatry and psychology suggest that depressed mood in clinical depression is similar to mild sadness experienced in everyday life, but more intense and persistent. We evaluated this concept using measures of average mood and mood instability. Method: We prospectively measured low and high moods using separate visual analogue scales twice a day for 7 consecutive days in 137 participants from 4 published studies. Participants were divided into a non-depressed group with a Beck Depression Inventory score of ≤ 10 (n = 59) and a depressed group with a Beck Depression Inventory score of ≥ 18 (n = 78). Mood instability was determined by the mean square successive difference statistic. Results: Mean low and high moods were not correlated in the non-depressed group, but were strongly positively correlated in the depressed group. This difference between correlations was significant. Low mood instability and high mood instability were weakly positively correlated in the non-depressed group and strongly positively correlated in the depressed group. This difference in correlations was also significant. Conclusion: The results show that low and high moods, and low and high MI, are highly correlated in people with depression compared with those who are not depressed. Current psychiatric practice does not assess or treat mood instability or brief high mood episodes in patients with depression. New models of mood that also focus on mood instability will need to be developed to address the pattern of mood disturbance in people with depression